Assessment of the purity and characteristics of rat splenic T cells isolated by one-step discontinuous gradient of percoll - Sulaiman Ngongu Depamede Depamede (Indonesian Center for Animal Research and Development (ICARD), 2010)
T cells isolated from spleen lymphocytes of rat (Rattus rattus) have been commonly used in an immunological research. However the T cells are still contaminated with other splenic cells. Therefore a simple and reliable technique to isolate the T cells in one step process is needed. The aim of the present study was to assess whether T cells isolated from spleen lymphocytes of rat as a model by means of discontinuous density gradient of Percoll could give pure T cells with their activities as needed in an immunological research. Isolation was carried out in 5 density gradients of Percoll i.e. 1.052, 1.063, 1.075, 1.085, and 1.122 g/ml. The purity of the cell fractions was determined by immunocytochemistry and fluorescence-activated cell sorting (FACS) methods. The activity of each lymphocyte fraction was determined through cell proliferation assays by culturing the cells in the presence of phytohemaglutinin (PHA) and Concanavalin A (Con A) as T cells inducers. The FACS results show that fraction I and II were found to contain mostly B cells and macrophages. The fractions were obtained on the layers of gradient 1.052/1.063 and 1.063/1.075. Fraction III (gradient 1.075/1.085) contain T cells (43.2%) which consisted of CD4 (34.4%) and CD8 (18.6%), B cells (36.5%), and macrophages (10.0%). Fraction IV was strongly expressed T cell receptors (76.2%) which consisted of CD4 (63.6%) and CD 8 (20.0%), while B cells were found 20.0% and macrophages just about 0.6%. The activity of T cells as expressed by their respond to PHA and Con A shown that fraction III gave the most positive response, while fraction IV which contained the most ‘pure’ T cells gave less activity. From the present study it can be concluded that the discontinuous density gradient of Percoll method can be used to isolate and purify T cells in one step process. Furthermore, the present study indicated that T cells to proliferate in response to mitogen require other immune cells such as B cells and macrophages. Key words: Percoll, Lymphocyte, T Cell, Rat, Mitogen